Technological innovation in the teaching and processing of lsps: proceedings of tislid'10 - TALAVÁN ZANÓN, Noa (Colección de libros electrónicos en Xebook, 2011)
The present book is a compilation of articles corresponding to the papers presented at TISLID ?10, the First International Workshop on Technological Innovations for Specialised Linguistic Domains, which took place in Spain on October 21-22, 2010. The program of TISLID?10 was established to offer the research and teaching community an opportunity to exchange knowledge and experiences and promote face-to-face academic debate on effective and innovative ways to design and develop CALL systems and NLP systems for sublanguages or specialized linguistic domains. The inclusion of basic research undertaken in educational institutions and research centers, together with the applied research and commercial development undertaken by publishers, e-Learning companies, etc. was considered a priority.